(untitled) (GEON Journal (Management, Organizations and Business), 2015)
Publicity is a mechanism that influences the purchase of a product or service to complete a transaction. Currently renowned artists in national and international fields influence the generation of credibility in the negotiation between the suppliers and the consumer. These celebrities show their image through advertising products which guarantees the success of negotiation. The article presents a proposal for the measurement of the effectiveness of this advertising in the consumer based on the scale of Ohanian (1990), considering the case of Shakira and James Rodríguez as personalities who manage its image through publicity and affecting the credibility of the products or services that they promote.